THE AVENGING GOD OF NAHUM AS COMFORTER OF THE TRAUMATIZED - K Spronk (Acta Theologica)
In this article dedicated to my esteemed colleague Fanie Snyman, I want to contribute to the fascinating field of the study of biblical literature and the hermeneutics of trauma. Instead of focussing on the more common reference to prophets such as Jeremiah who helped people cope with the traumatic experience of the Babylonian exile, I will pay attention to the very different message of Nahum to the Judeans who suffered under Assyrian tyranny. This prophecy is less popular and often condemned for the way in which it portrays YHWH as a violent god. This even seems to approve of, and therefore also incite sexual abuse of women. I will attempt to demonstrate that the trust in YHWH as both a good god and an avenger of the evil deeds of the Assyrians functions as a prerogative to restore the faith of the traumatized Judeans. The way in which YHWH’s revenge is presented has an important function within this framework. Modern interpreters should be reluctant in criticizing it, because it can have a healing function in the specific situation of the traumatized.